Early Literacy Assessment For Children With Autism Spectrum Disorders At Preschool - Rizqi, Putri; Ummah, Umi Syaiful; Hastuti, Wiwik Dwi; Malizal, Zelynda Zeinab (Indonesian Scientific Publication, 2024)
Autism Spectrum Disorder is a disorder that causes children to experience obstacles in communication skills, starting from the child's language understanding. Where early assessment will help children with ASD to develop and improve their abilities, so early reading assessment needs to be carried out. Code-related abilities (such as letter knowledge, print concepts, and early writing) and meaning-related skills (such as vocabulary, recounting stories, and understanding) are used to evaluate early reading. The purpose of this study was to determine the early reading abilities of preschool children aged 3-5 years with ASD and also appropriate interventions according to their needs. This study uses a quantitative method of observation, interviews and document reviews to determine beginner reading assessment skills in children with ASD. The test was conducted on three preschool children aged 3 to 5 years: Kenzy, Excy, and Mikhael. From the results of this study, the early reading skills of children with ASD in Kenzy and Excy are limited to identifying consonants and vowels. At the same time, Michael only needs further reinforcement on several letters, and intonation is still flat. From the assessment results, multidisciplinary programs, phonological awareness, and natural developmental behavioural interventions (NDBI) can be given.